Sensors handbook - Soloman, Sabrie (New York : McGraw Hill Education, 2010)
"Completely updated with new sensor breakthroughs. The second edition of Sensors Handbook equips you with cutting-edge information on advancements in sensing technology and applications in various fields, including medical, geographical,environmental, industrial, semiconductor manufacturing, and mechanical engineering. This expert guide features new developments in nano MEM sensing, smart biosensing, CMOS sensor and silicon integration, chemical sensing for environmental applications,and more. With its comprehensive coverage, this revised classic now offers you a global picture of sensor technology and applications."
Chapter 1. Types and Classifications of Sensors and Control Systems -- Chapter 2. Fiber Optics in Sensors and Control Systems -- Chapter 3. Networking of Sensors and Control Systems in Manufacturing -- Chapter 4. The Role of Sensors and Control Technology in Computer-Integrated Manufacturing -- Chapter 5. Advanced Sensor Technology in Precision -- Chapter 6. Industrial Sensors and Control in Manufacturing -- Chapter 7. Sensors in Flexible Manufacturing Systems -- Chapter 8. Communications -- Chapter 9. MEMS Applications in Energy Management -- Chapter 10. The NANO/MEMS Program -- Chapter 11. MEMS in the Medical Industry -- Chapter 12. MEMS: Current and Future Technology -- Chapter 13. MEMS Advanced Research and Development -- Chapter 14. Functional Integration of Microsystems in Silicon -- Chapter 15. Automotive Applications of Microelectromechanical System (MEMS) -- Chapter 16. A Brief Study of Magnetism and Magnetic Sensors -- Chapter 17. The Fundamentals and Value of Infrared Thermometry -- Chapter 18. GMR: The Next Generation of Magnetic Field Sensors -- Chapter 19. Smart Civil Structures, Intelligent Structural Systems -- Chapter 20. True Online Color Sensing and Recognition -- Chapter 21. Fundamentals of Solid-State Presence-Sensing Technologies -- Chapter 22. Design and Application of Robust Instrumentation Sensors in Extreme Environments -- Chapter 23.Color Machine Vision -- Chapter 24. Monolithic Integrated Physical and Chemical Sensors in CMOS Technology -- Chapter 25. A Research Prototype of a Networked Smart Sensor System -- Chapter 26. Sensors and Transmitters Powered by Fiber Optics -- Chapter 27. A Process for Selecting a Commercial Sensor Actuator Bus as an Industry Interoperable Standard -- Chapter 28. A Portable Object-Oriented Environment Model (POEM) for Smart Sensors -- Chapter 29. New Generation of High-Temperature Fiber-Optic Pressure Sensors -- Chapter 30. Principles and Applications of Acoustic Sensors Used for Gas Temperature and Flow Measurement -- Chapter 31. Understanding and Applying Intrinsic Safety -- Chapter 32. Application of Acoustic, Strain, and Optical Sensors to NDE of Steel Highway Bridges -- Chapter 33. Long-Term Monitoring of Bridge Pier Integrity with Time Domain Reflectometry Cables -- Chapter 34. Sensors and Instrumentation for the Detection and Measurement of Humidity -- Chapter 35. Thermal Imaging for Manufacturing Process and Quality Control -- Chapter 36. The Detection of ppb Levels of Hydrazine Using Fluroscence and Chemiluminescence TechnFluorescence -- Chapter 37. Molecular Relaxation Rate Spectrometer Detection Theory -- Chapter 38. Current State of the Art in Hydrazine Sensing -- Chapter 39. Microfabricated Sensors: Taking Blood Testing out of the Laboratory -- Chapter 40. Closed-Loop Control of Flow Rate for Dry Bulk Solids -- Chapter 41. Weigh Belt Feeders and Scales: The Gravimetric Weigh Belt Feeder -- Chapter 42. Low-Cost Infrared Spin Gyro for Car Navigation and Display Cursor Control Applications -- Chapter 43. Quartz Rotation Rate Sensor: Theory of Operation, Construction, and Applications -- Chapter 44. Fiber Optic Rate Gyro for Land Navigation and Platform Stabilization -- Chapter 45. Composite Sensor Optics in Advance Astronomical Observations -- Chapter 46. Microfabricated Solid-State Secondary Batteries for Microsensors -- Chapter 47. High-Temperature Ceramic Sensors -- Chapter 48. Microfabricated and Micromachined Chemical and Gas Sensor Developments -- Chapter 49. Electro-formed Thin-Film Silica Device as Oxygen Sensors -- Chapter 50. Using Leg-Mounted Bolt-On Strain Sensors to Turn a Tank into a Load Cell -- Chapter 51. CFive New Technologies for Weighing Instrumentation -- Chapter 52. Multielement Microelectrode Array Sensors and Compact Instrumentation Development at Lawrence Livermore National Laboratory -- Chapter 53. Enabling Technologies for Low-Cost, High-Volume Pressure Sensors -- Chapter 54. A Two-Chip Approach to Smart Sensing -- Chapter 55. Specifying and Selecting Semiconductor Pressure Transducers -- Chapter 56. Introduction to Silicon Sensor Terminology -- Chapter 57. Silicon Sensors and Microstructures: Integrating an Interdisciplinary Body of Material on Silicon Sensors -- Chapter 58. Understanding Silicon Processing and Micromachining -- Chapter 59. Universal Sensors Technology: Basic Characteristics of Silicon Pressure Sensors -- Chapter 60. Advanced Sensor Designs -- Chapter 61. Silicon Microstructures -- Chapter 62. Computer Design Tools -- Chapter 63. Signal Conditioning for Sensors -- Chapter 64. Advances in Surface Micromachined Force Sensors -- Chapter 65. Distributed, Intelligent I/O for Industrial Control and Data Acquisition: The Seriplex Sensor/Actuator Bus -- Chapter 66. Innovative Solar Cell MIMICS Photosynthesis -- Chapter 67. Quartz Resonator Fluid Monitors for Vehicle Applications -- Chapter 68. Overview of the Emerging Control and Communication Algorithms Suitable for Embedding into Smart Sensors -- Chapter 69. Applications of Conductive Polymer-Based Chemical Sensors -- Chapter 70. Modeling Sensor Performance for Smart Transducers -- Chapter 71. Infrared Gas and Liquid Analyzers: A Review of Theory and Applications -- Chapter 72. Infrared Noncontact Temperature Measurement: An Overview -- Chapter 73. Quality Control Considerations -- Chapter 74. Universal Drug and Food Cleanliness Using HPLC Sensing Detection -- Chapter 75. Micro-system Technologies.
Includes bibliographical references and index.
Keywords: DETECTORS HANDBOOKS, MANUALS, ETC